Ultrassom terapêutico de alta potência no tratamento da lipodistrofia localizada abdominal: ensaio clínico randomizado duplo cego - Siqueira, Karina da Silva (2019)
Overweight, defined as the existence of more adipose tissue than the healthy ideal, has recently reached epidemic proportions globally, with more than one billion adults in this condition or obese. In order to reduce and attenuate localized lipodystrophy, several minimally invasive techniques have been developed in order to reproduce the efficacy of liposuction, with therapeutic ultrasound being one of the main resources used. The objective of the present study was to evaluate the effects of highpower therapeutic ultrasound in the treatment of localized abdominal lipodystrophy in two ways; when used alone, with neutral gel compared to the effects of ultrasonic therapy with caffeine gel at 5 %, a technique known as phonophoresis. 90 women aged 18-40 years participated in the study and were randomly assigned to two different groups; Group A and Group B that differed by the numbering of the lead gel batches used in the application. These patients underwent previous evaluation consisting of anamnesis, perimetry, bioimpedance, ultrasound examination and laboratory blood tests (complete lipidogram, creatinine and Vitamin D) and the same evaluation was repeated at the end of the protocol of 10 sessions of Ultrasound Avatar Four – 3 MHz with intensity of 2.0 W/cm² and power of 30 W. At the end of the statistical analysis the groups were identified, being group A gel with caffeine and group B neutral gel. Analyzing the evaluation parameters, there was a significant reduction in both perimetry (p < 0.001) and adipose tissue thickness measurements performed by ultrasonography (p < 0.001). The laboratory tests presented significant alteration only of the complete lipidogram, but without statistical significance (p> 0.05). When comparing the groups with each other, there was no statistically significant difference in any of the analyzed parameters, which indicates that the high-power ultrasonic therapy is efficient to reduce localized lipodystrophy, regardless of whether it is applied with neutral gel or with active.